Crop yield and nutrient balance influenced by shoot biomass management and pig slurry application - Carla M. Pandolfo (Revista Brasileira de Engenharia Agrícola e Ambiental - Agriambi, 2016)
ABSTRACT Crop systems that export large amounts of nutrients from the farm may require higher doses of animal manure than those needed for grain production. This study aimed to evaluate the yield of crops and to determine the simplified nutrient balance in three management systems of shoot biomass of crops (cover-grain, cover-silage and hay-silage) associated with five fertilization treatments (control, soluble fertilizer and three doses of pig slurry). The experimental design was a split plot, arranged in randomized blocks with four replicates. The management systems of shoot biomass did not affect the yield of the winter pasture, but there was an increase in yield with the application of pig slurry. The summer crops responded differently to fertilization, depending on the purpose for which they were grown, whether for grain or silage. In the three management systems of shoot biomass, there was an excess of Zn and Cu from the application of 25 m3 ha-1; N from 50 m3ha-1; and P, K and Ca + Mg at the dose of 100 m3ha-1.